Sistem Informasi Kegiatan Karang Taruna Berbasis Web (Studi Kasus Karang Taruna Boedi Utomo) - Fahrurozi, Muhammad; Al Ikhsan, Safaruddin Hidayat; Rachmawati, Fitria (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research focuses on improving the quality of life in communities through empowerment in various sectors, including youth involvement. However, challenges such as high costs and the risk of human error in information dissemination and documentation management often hinder the effectiveness of youth organizations like Karang Taruna Boedi Utomo. This study aims to develop a web-based information system that is efficient and effective for managing the organization’s activities and budget. The system is designed to address transparency and efficiency issues faced by Karang Taruna by integrating information technology to simplify data access and management. The research method employed is the waterfall model, ensuring a systematic and sequential software development process. The results of the needs analysis and system design show that the system successfully meets the needs of Karang Taruna Boedi Utomo, improving transparency and reducing the risk of errors in budget management and activity documentation. With the implementation of this system, it is expected to support the organization’s operations, contribute to increased effectiveness, and maximize the role of youth in the community.